Impact of Human–Animal Interactions on Psychological and Physiological Factors Associated With Veterinary School Students and Donkeys - Artemiou, Elpida; Hutchison, Pippa; Machado, Marcus; Ellis, Daria; Bradtke, Jennifer; Pereira, Mary Mauldin; Carter, Julia; Bergfelt, Don (Frontiers in Veterinary Science, 2021)
There has been an increased interest in evaluating human-animal interactions and assessing the mutual health and wellbeing benefits of these. This study involved first-year female and male veterinary school students not paired (n=58) or paired (n=25) with immature (≤9 mo) donkeys (n=13) who engaged in three different types of interactions (hands-off remote learning, hands-on passive learning, and hands-on active learning) for 30 min each during Week 2 (Time 1), Weeks 5-8 (Time 2), and Week 12 (Time 3) over three, 15-week periods. Student psychological data involved the Penn State Worry Questionnaire (PSWQ) scores collected from the interactive (student-donkey pairs) and non-interactive (no student-donkey pairs) groups and modified Comfort from Companion Animals Scale (CCAS) scores collected from the interactive group during Times 1, 2, and 3. Donkey physiological data involved collection of saliva within 10 min pre- and post-interaction during Times 1, 2, and 3 in association with the different types of interactions for analysis of cortisol. There were no significant effects of the various times and types of interactions on CCAS scores. While there were no significant effects of group and types of interactions on PSWQ scores, there was an effect (P=0.01) of time. Overall mean PSWQ scores were significantly lower during Week 12 than Week 2. Correspondingly, there were no effects pre- vs post-interaction within or among times on cortisol concentrations, but there was an effect (P=0.02) of the type of interaction. Mean concentrations were significantly lower with the hands-on passive and hands-on active learning versus than the hands-off remote learning. Although preliminary, the results continue to support the mutual benefits of health and wellbeing associated with human-animal interactions as indicated by a decrease in level of worry for students by Week 12 or later during the semester, which corresponded with a decrease in concentrations of saliva cortisol in immature donkeys when the interactions involved hands-on activities also later during the semester.